Optimizing Business Potential: Digital Marketing Training for Online Success in Educational Tourism in Kampung Lele District of Kediri - Selviasari, Rike; Ambarwati, Diana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to increase the knowledge and skills of MSME players in the field of digital marketing, especially Search Engine Optimization (SEO). This research was carried out using training methods for Karang Taruna and employees of Kampung Lele Tourism in Kediri Regency. The research results show that SEO training is effective in increasing participants' knowledge and skills. Training participants are able to understand the concepts of SEO, on-page SEO, and off-page SEO. Participants are also able to apply SEO on the Kampung Lele Tourism website.